Estudo das variáveis hidrometeorológicas associados a fatores ambientais: bacia hidrográfica do Rio Xingu - RIBEIRO, Bárbara Farias (2021)
The question of the changes in rivers’ levels (floods and ebbs) and the variability of rainfall in the Amazon region is a major problem, as it directly affects the local population. This highlights the importance of environmental planning, including adequate management for the basins that make up this region. In the Amazon region, the hydrographic basin of the Xingu River, which is located in the state of Mato Grosso and Pará, develops in the south-north direction. The objective of this work is the use of space-time models with hydro meteorological variables (precipitation and flow) associated with environmental factors (such as land use) to assist in the characterization of areas in the Xingu River basin. For statistical analysis of pluviometric and fluviometric data, regression models were used in order to assess trends for these variables, study of spatial correlation through geostatistics with mapping of variables and use of spatial models (spatial econometrics), and the k-means method (formation of homogeneous groups), using Microsoft Excel software and R-The R Project for Statistical Computing 2015. According to the annual historical series (1988 to 2017), it was observed that the annual average precipitation in the basin is between 1273.2 mm to 2645.3 mm. While the monthly average variability shows the least rainy period characterized by the months of May to October, fluctuations are observed with minimum values of 17.4 mm to 155.6 mm causing the drought period in the area. The basin has the highest flows in the months of February, March and April, with the highest value in March (7937.5 m³ / s). The trend study for both variables showed that the average remained constant, that is, there was no trend. The Moran's global indices calculated for rainfall (I = 0.7521) and flows (I = 7833) indicate that there is a positive spatial correlation for these two variables. The land's use with the most predominance in the basin is forest with (75, 4%), concentrating in almost all the territorial extension of the basin, predominating in the cities located in central and in the cities concentrated in the north part of this region. The results obtained in this study may contribute to greater knowledge of possible relationships between hydro meteorological and environmental variables in the Xingu basin and how much these results can help the population near of the study area with the problems of the variability in the river level, heavy rains and their possible damage to the local community related to the economic, material and environmental factors.